The Influence of Entertainment Tax, Advertising Tax and Parking Tax on Yogyakarta City Regional Tax Revenue - Adelia, Sefica Putri (CV. Rayyan Dwi Bharata, 2024)
Tax is a region's income that is sourced from wealth and resources managed by the local government which is a source of Regional Original Income. This research aims to determine the effect of entertainment tax revenue, advertising tax and parking tax on regional tax revenue in the city of Yogyakarta. The population in this study is entertainment tax revenue, advertising tax, parking tax in the city of Yogyakarta. The research period starts from 2020 - 2022. The technical analysis of this data uses a multiple linear regression test with local tax revenue as the dependent variable as well as entertainment tax and advertising tax. The results of the research show that the entertainment tax variable and regional tax revenue do not have a significant influence, while the advertising tax variable and the parking tax variable have a significant influence on regional tax revenue.